(untitled) (FuLiA/UFMG, 2022)
“Brasil na Arquibancada” is a Project conceived in 2011 by Ludens (Interdisciplinary Research Center on Football and Playful Modalities), linked to the Department of History at University of São Paulo. From May to December 2012, a group of investigators focused on the 40 clubs that, at the time, competed in the Brazilian Championships of Series B and C, in order to capture how cheering modalities in Brazil on the eve of the World Cup from the 2014 FIFA World. This text, in addition to initially commenting on some aspects of the project, offers three memorialists reports in chronicle format, seeking to present to the readership some temporalities and spatiality of the 3rd national football, in cities of the States of Minas Gerais and São Paulo.